Clinical features and outcomes of patients with follicular lymphoma: A real-world study of 926 patients in China - Gao, Fenghua; Zhang, Tingting; Liu, Xia; Qu, Zhenjie; Liu, Xianming; Li, Lanfang; Qiu, Lihua; Qian, Zhengzi; Zhou, Shiyong; Gong, Wenchen; Meng, Bin; Ren, Xiubao; et al. (Frontiers in Oncology, 2022)
Background：The data about the clinical features and outcomes of Chinese patients with follicular lymphoma (FL) are limited. Here, we conducted a retrospective study to explore the initial treatment strategies and clinical outcomes of Chinese patients with FL in the real-world. Method: This study included FL patients who were newly diagnosed in Tianjin Medical University Cancer Institute and Hospital from March 2002 to August 2020. Results：A total of 926 FL patients were enrolled. The median age was 54 years old and the majority Chinese FL patients had advanced-stage disease and Eastern Cooperative Oncology Group(ECOG)≤ 1, but less frequently infiltrated bone marrow. After median 38-month follow-up, the 5-year progressive-free survival (PFS) and overall survival (OS) of grade1-3a were 57.8% and 88.7%, respectively, which both are similar to those reported in previous Chinese and Western studies. The co-existence at diagnosis of FL and diffuse large B-cell lymphoma (DLBCL) components (FL/DLBCL) were associated with poor outcomes. The FL grades and proportion of DLBCL component in FL/DLBCL did not impact on PFS and OS. The most common regimen with great efficacy and risk-benefit was RCHOP-like followed by R maintenance regimen. The 5-year cumulative hazard of histological transformation (HT) was 4.7% (95% CI,3.5-5.9), median time to transformation was 23.5 months (range,2-146 months) after diagnosis. Three-year survival following transformation was 55% (95% CI:40-70). Patients with stage III-IV, β2 microglobulin (β2-MG) elevated, and B symptoms seemed to be more prone to progress within 24 months of front-line therapy (POD24). The FLIPI-2 showed the highest specificity to predict POD24, reflecting the prediction of correctly classifying as low-risk patients, but the FLIPI had the highest sensitivity to predict the risk of progression at the critical. Conclusions: We revealed the clinical characteristics and outcomes of FL patients in the real-world in China, which may provide novel data on prognostic factors and primary treatment of FL, applicable to routine clinical practice.